Translational systems biology of inflammation: potential applications to personalized medicine. (September 2010) - Mi, Qi; Li, Nicole Yee-Key; Ziraldo, Cordelia; Ghuma, Ali; Mikheev, Maxim; Squires, Robert; Okonkwo, David O; Verdolini-Abbott, Katherine; Constantine, Gregory; An, Gary; Vodovotz, Yoram
A central goal of industrialized nations is to provide personalized, pre-emptive and predictive medicine, while maintaining healthcare costs at a minimum. To do so, we must confront and gain an understanding of inflammation, a complex, nonlinear process central to many diseases that affect both industrialized and developing nations. Herein, we describe the work aimed at creating a rational, engineering-oriented and evidence-based synthesis of inflammation geared towards rapid clinical application. This comprehensive approach, which we call 'Translational Systems Biology', to date has been utilized for in silico studies of sepsis, trauma/hemorrhage/traumatic brain injury, acute liver failure and wound healing. This framework has now allowed us to suggest how to modulate acute inflammation in a rational and individually optimized fashion using engineering principles applied to a biohybrid device. We suggest that we are on the cusp of fulfilling the promise of in silico modeling for personalized medicine for inflammatory disease.